Modeling technique of capacitive discharge pumping of metal vapor lasers for electrode capacitance optimization; Review of Scientific Instruments; Vol. 83, iss. 5 - Gubarev F. A. Fedor Aleksandrovich; Evtushenko G. S. Gennady Sergeevich; Vuchkov N. K.; Sukhanov V. B. Viktor Borisovich; Shiyanov D. V. Dmitry Valeryevich (2012, 2012)
To estimate optimum gas discharge tube (GDT) electrode capacitance of metal vapor lasers (MVLs) pumped by a longitudinal capacitive discharge, we offer to use series connection of capacitors to the electrodes of a conventionally pumped GDT with inner electrodes. It has been demonstrated that the maximum output power in CuBr lasers is obtained when the capacitances of high-voltage and ground electrodes are equal. When using a model circuit an average output power reaches 12 W that suggests the possibility of generating high average output power (>10 W) in MVLs pumped using a capacitive discharge.